The Digital Sabbath Project - Paris, Lisa; Morris, Julia (Fremantle Arts Centre (The Moores is a subsidiary of the FAC), 2020)
This project aimed to determine the impact of a Digital Sabbath (DS) intervention on teachers' wellbeing, if teachers spend one day a week 'unplugged' from technology. The research showed a DS practice allowed participants to slow down and become more observant of their environments. Some faced challenges with the practice, including questions from family and friends about why they would wish to engage with the practice – a sign of how pervasive technology is. It was difficult to stay ‘unplugged’ for a full 24 hours, with participants suggesting smaller blocks of time may be more achievable. The creative research component (over 50 artworks) translated these findings for the general public, encouraging broad dissemination of the results. Despite the known affordances of Arts-based Education Research (ABER), its use still remains uncommon in Australia. This project innovated the researchers’ established practice and advocated for the inclusion-normalisation of ABER practice in the Australian setting.